Poverty permanence among European youth - Daria Mendola; Annalisa Busetta; Arnstein Aassve (University of Essex, Institute for Social and Economic Research (ISER), 2008)
Previous studies suggest that Scandinavian countries are the ones with the highest rates of youth poverty in Europe. This somewhat unexpected finding prompts the question whether the incidence of poverty is an appropriate measure of youth disadvantage. Instead of considering poverty rates we define here youth disadvantage in terms of the number of periods an individual is recorded to be below the poverty line. Using the European Community Household Panel, individuals are classified into different groups of poverty permanence, each reflecting severity of social disadvantage. Based on these categories we implement a generalized ordinal logit model to assess the various factors associated with social disadvantage among youth. In contrast to previous research, we find little evidence to suggest that young individuals in Scandinavian countries suffer higher levels of social disadvantage. Moreover there is no significant gender difference in Conservative and Social Democratic welfare regimes, but significant difference in Mediterranean and Liberal countries. As previous studies suggests, young individuals living arrangements matter.
Keywords: 330